American Society of Biomechanics (2006)
The American Society of Biomechanics (ASB) was founded in October 1977 by a group of 53 scientists and clinicians. There are several regional and national associations - the American College of Sports Medicine, the American Society of Mechanical Engineers, and the Orthopaedic Research Society, for example, which regularly or occasionally assign portions of their meetings to biomechanics. These however, are generally attended by those people associated with the parent field. As a result, there is little opportunity for the kind of exchange between people working in different fields of application that would clearly benefit all concerned. The American Society of Biomechanics was formed to meet this need.